(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Small business and private entrepreneurship play a decisive role in the economic modernization of Uzbekistan. In the context of market reforms, employment growth, regional development, poverty reduction, innovation, and export diversification, the expansion of small business activity has become one of the key priorities of national economic policy. Small enterprises and private entrepreneurs are not only sources of income for households but also important actors in creating competitive markets, improving the quality of goods and services, and increasing the flexibility of the national economy. In Uzbekistan, the economic importance of this sector is especially high because small business connects urban and rural economies, absorbs labor resources, stimulates domestic demand, and creates opportunities for self-employment. According to the National Statistics Committee, in January–December 2025, small business entities generated 923,514.6 billion soums in GDP and their share in total GDP reached 52.2 percent. Their largest sectoral contribution was observed in agriculture, forestry and fisheries, construction, services, and industry. This shows that small business is not a secondary element of the economy, but one of its structural foundations. However, the further development of this sector requires better access to finance, stronger institutional support, digitalization, fair competition, and regional policy differentiation.